Analisis Eksegetis Makna Allon Paraklēton dalam Injil Yohanes: Signifikansi Kehadiran Roh Kudus sebagai Pengganti Personal Kristus - Rosalia Enny Astuti; Laurentius Prasetyo (Sekolah Tinggi Teologi Kanaan Nusantara, 2026)
This study aims to systematically reconstruct the doctrine of the Holy Spirit (Pneumatology) in the Gospel of John, specifically through an analysis of the term Allon Paraklēton, and to evaluate its relevance for spiritual life in the contemporary era. As a qualitative study, this research employs a literature review design, utilizing theological hermeneutics and exegetical analysis of primary Biblical texts and systematic theology literature. The findings, established through source triangulation, emphasize that the term allon specifically refers to